TAJIKISTAN: NEW STABILITY THREATS AND HOW TO AVOID THEM - MAKHMADOV, Abdurakhmon; KHIDIROVA, Makhfirat (CENTRAL ASIA AND THE CAUCASUS, 2005)
Today, life in Tajikistan, an independent country and an entity of international relations which has left the stage of civil confrontation behind, has changed in all its aspects. Indeed, no stage of human society’s development is free from potentially conflicting factors. If tapped in the right way, the contradictions may even help the country to advance. Even though the domestic conflict was settled peacefully, the problems associated with the current political processes are still lingering; they should be successfully addressed on time, otherwise they may develop into stability threats. Poverty of a considerable part of the republic’s population is one such problem, although today its level is much lower than the 82 percent registered in 1997. It is much easier to involve poor people in criminal activities or treason; they can fall prey to the manipulations of rich criminal or terrorist groups, since it is easy to tempt them with even small sums of money. In the final analysis, this could turn into a destabilizing factor in any society. This is especially true of Tajikistan which, for geopolitical, regional, ethnic, and religious reasons, attracts all sorts of forces trying to put pressure on it. The problem is obviously of great political importance. Poverty is conducive to corruption in all echelons of power; it breeds criminal groups, which are inclined to divide zones of influence, and intensifies drug trafficking. All this may finally destroy the country’s statehood. Tajikistan’s leaders are doing their best to raise the standard of living; they are employing the medium-term Strategy for Reducing Poverty, which envisages: